2015
DOI: 10.1074/mcp.m115.050922
|View full text |Cite
|
Sign up to set email alerts
|

Serum Glycoprotein Biomarker Discovery and Qualification Pipeline Reveals Novel Diagnostic Biomarker Candidates for Esophageal Adenocarcinoma

Abstract: We report an integrated pipeline for efficient serum glycoprotein biomarker candidate discovery and qualification that may be used to facilitate cancer diagnosis and management. The discovery phase used semi-automated lectin magnetic bead array (LeMBA)-coupled tandem mass spectrometry with a dedicated data-housing and analysis pipeline; GlycoSelector (http://glycoselector.di. uq.edu.au). The qualification phase used lectin magnetic bead array-multiple reaction monitoring-mass spectrometry incorporating an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 66 publications
4
58
0
Order By: Relevance
“…Recently, several research groups have reported certain genes and signaling molecules that are potentially involved in EC initiation and progression (24,25). These molecular targets may provide significant clues for early diagnosis, prognosis and new targeted therapies (26)(27)(28). Previous studies have found that TGM3 expression is downregulation in head and neck cancer, laryngeal carcinoma and oral squamous cell carcinoma (29)(30)(31)(32), other reports found that TGM3 expression is decreased in EC tissues compared with normal tissues (29).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, several research groups have reported certain genes and signaling molecules that are potentially involved in EC initiation and progression (24,25). These molecular targets may provide significant clues for early diagnosis, prognosis and new targeted therapies (26)(27)(28). Previous studies have found that TGM3 expression is downregulation in head and neck cancer, laryngeal carcinoma and oral squamous cell carcinoma (29)(30)(31)(32), other reports found that TGM3 expression is decreased in EC tissues compared with normal tissues (29).…”
Section: Discussionmentioning
confidence: 97%
“…Michelle's studies have focussed on the potential of disease-related glycoproteins as potential markers of early stage disease. To assist in this goal a lectin magnetic bead array (LeMBA) coupled with a mass spectrometry biomarker pipeline was developed which revealed novel potential diagnostic biomarkers for EAC [3]. The data were further validated in independent cohorts [4] and a candidate biomarker panel for BE surveillance developed.…”
Section: Session B Proteomics: Towards the Clinicmentioning
confidence: 99%
“…Glycoproteins have been shown to be critical to cell adhesion, 63,64 differentiation 65 and growth, and they have also been used as new targets for therapeutics and diagnostics. 66 Ousmer et al utilised a Negishi cross-coupling to form a p-(Cglucopyranosyl)phenylalanine derivative (Scheme 17). 67 An iodo-substituted phenylalanine derivative was successfully coupled to a glucal 41 in an excellent 90% yield.…”
Section: Synthesis Of Complex Amino Acidsmentioning
confidence: 99%